Fiscal Deficit And Inflation: A Macroeconomic Correlation Study In Indonesia - Rita Sugiarti; Heru Subiyantoro (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the relationship between fiscal deficit and inflation in Indonesia during the 2000-2023 period. Using secondary data from Bank Indonesia and the Ministry of Finance, this study applies correlation and regression analysis methods to test the linkage between these variables. The results show a moderate positive correlation (r=0.61) between fiscal deficit and inflation in Indonesia, with significant but non-linear influences across different periods. Further analysis reveals that this relationship is moderated by factors such as economic growth, Bank Indonesia's monetary policy, and external conditions. These findings imply the importance of synchronizing fiscal and monetary policies to maintain Indonesia's macroeconomic stability, as well as considering structural aspects such as production capacity and government spending efficiency in fiscal deficit management.